THE ROLE OF PUBLIC AGRICULTURAL SPENDING AS A PANACEA FOR AGRICULTURAL SUBSECTOR PRODUCTION: EMPIRICAL EVIDENCE FROM CAMEROON - Udeme Henrietta UKPE; Raoul Fani DJOMO CHOUMBOU; Rayner TABETANDO; Emmanuel Nkwi GAMA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the paper was to analyse the role of public agricultural spending as a panacea for agricultural subsector production in Cameroon. The data were taken from World Bank development database and processed using growth model, and error correction model. Despite the agricultural sector's significant contributions to the country's economy throughout the years, the country has made little headway in reducing it. Recent interest in the relationship between government spending and economic output has not focused on the central question of whether government spending, particularly agricultural spending increases agricultural subsector output or otherwise. With instantaneous and compound growth rates of 6.7 percent and 6.93 percent, 3.03 percent and 3.08 percent, 13.66 percent and 14.64 percent, respectively, the results demonstrated stagnation in agricultural and livestock subsector production and labor. In contrast, public agriculture spending increased at a faster rate, with instantaneous and compound growth rates of 6.09 percent and 6.27 percent, respectively. In the short run, agricultural land, labor, and public agricultural spending all have a substantial impact on animal productivity. Cutting public agricultural spending by 25% is the most cost-effective way to maintain crop and livestock production in the short term. Incentives such as tax reductions and infrastructure development should be established to attract more private investors, knowledge transfer, and significant capital inflows to ensure the agricultural sub-long-term sector's viability. In the short term, privatization of the government's agricultural development projects will be critical for efficient use of public resources.